1989
DOI: 10.1093/nar/17.5.1805
|View full text |Cite
|
Sign up to set email alerts
|

Calf thymus DNA polymerase δ Independent of proliferating cell nuclear antigen (PCNA)

Abstract: DNA polymerase delta from calf thymus was purified under conditions that minimized proteolysis to a specific activity of 27,000 units/mg. The four step isolation procedure included phosphocellulose, hydroxyapatite, heparin-Sepharose and FPLC-MonoS. This enzyme consists of four polypeptides with Mr of 140, 125, 48 and 40 kilodaltons. Velocity gradient sedimentation in glycerol removed the 48 kDa polypeptide while the other three sedimented with the DNA polymerase activity. The biochemical properties of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Its catalytic properties are clearly different from those of DNA pol E (or 82), which we have characterized from HeLa cells (8,10) and others have studied from calf thymus (6,7,19,25). The purification of DNA pol and E simultaneously from the same HeLa extract and the differences in the partial peptide maps of their large subunits support the premise that the enzyme proteins are different in spite of the weak cross-reactivity with a polyclonal antibody and possible common motifs in peptide maps found earlier between HeLa DNA pol E and calf thymus DNA pol 8 (11).…”
Section: Discussionmentioning
confidence: 76%
“…Its catalytic properties are clearly different from those of DNA pol E (or 82), which we have characterized from HeLa cells (8,10) and others have studied from calf thymus (6,7,19,25). The purification of DNA pol and E simultaneously from the same HeLa extract and the differences in the partial peptide maps of their large subunits support the premise that the enzyme proteins are different in spite of the weak cross-reactivity with a polyclonal antibody and possible common motifs in peptide maps found earlier between HeLa DNA pol E and calf thymus DNA pol 8 (11).…”
Section: Discussionmentioning
confidence: 76%
“…Whereas pol ␦ is processive only in the presence of PCNA, pol ⑀ is very active even in the absence of PCNA. Previous studies have reported that pol ⑀ is completely unresponsive to the addition of PCNA (20,35); however, more detailed kinetic studies have shown that PCNA can also stimulate the processivity of pol ⑀ and that pol ⑀ interacts with PCNA, increasing its rate of nucleotide incorporation (36). In the presence of RF-C and ATP, pol ⑀, like pol ␦, is able to form a stable complex with PCNA at the 3Ј-end of the primer, called pol ⑀ holoenzyme (30,37).…”
mentioning
confidence: 99%
“…Recently another polymerase, also called Pol-6, which does not require PCNA, has been isolated from several mammalian sources (17)(18)(19)(20). These different Pol-8 preparations share some common properties, including 3' -+ 5' exonuclease activity and resistance to butylphenyl-dGTP (BuPh-dGTP) and butylanilo-dATP.…”
mentioning
confidence: 99%